Basic social and psychological peculiarities of a couple having a conscious large family - Chepelieva, Nadiya (Psychological Prospects Journal, 2021)
Purpose. The article focuses on theoretical and empirical analysis of certain social and psychological peculiarities of married couples having conscious large families. Methods. Theoretical social and psychological analysis of the phenomenon of a large family concerning the characteristics that determine and contribute to the conscious choice regarding a family having many children. The developed questionnaire and conducted survey are based on theoretical analysis, which includes several essential blocks: questions about the decision to have many children, difficulties of a large family, peculiarities of internal familial and social support.Results. The social and psychological peculiarities of people who have consciously become parents of 3 or more children feel in this their call, need, and desire are based on high reproductive initial settings in most respondents are theoretically and empirically determined. It has been found out that transition of a family to have many children may have a place at different stages, but it can be argued that a conscious large family should be considered as a planned one. It is confirmed by the statistics, the social and cultural mechanisms, according to which the presence of three or more children is that level that predetermines the viability of a society and a family.The survey data of prosperous large families have been analyzed, where the vital stability of the family system is observed; women are engaged in professional activities and are self-realized, and at the same time combine motherhood and raising children, because in the contemporary world the value of parenthood competes with other values, particularly with successful professional activity and career. Certain social settings and stereotypes regarding a large family have been determined. The contemporary viewpoints of the society are presented, according to which the function of a woman is not only motherhood and home, but also other opportunities for implementation of the potential inherent in her. The basis of a couple having a conscious large family is the personality and social maturity of its members.Conclusions. The paper formulates social and personality characteristics, problems and difficulties faced by conscious parents having large families. It has been proved that although social support plays a significant role, first it is necessary to form it based on psychological readiness, conscious choice, opportunities for self-realization of such families and parents in particular.